Strategi Manajemen Koleksi Dinas Perpustakaan dan Arsip Kabupaten Deli Serdang - Sari, Nimas Fatma; Sayekti, Retno; Faturrahman, Muslih (ARZUSIN, 2023)
This study discusses the collection management strategy of the Deli Serdang Regency Library and Archives Service. The purpose of the study was to determine the strategy for procurement of collections and the obstacles faced in procuring collections at the Department of Library and Archives of Deli Serdang Regency. This type of research is a qualitative research with a descriptive approach. The technique used in data collection is by conducting observations, interviews, and documentation. While the data analysis technique is done by doing data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of the procurement of collections at the Library and Archives Service of Deli Serdang Regency begins with planning by conducting a survey to visitors and providing a complaint box so that the collections owned are relevant to the needs of users. Organizing in the procurement of collections is done based on the job description. Implementation of collection procurement is done through purchases with publishers and through donations not on request. Supervision in the procurement of collections is carried out by the Head of Service who is assisted by the Head of Division and supervision of the collections owned is carried out by officers in the field of procurement of library materials. Evaluation is done by matching the evaluation is done by matching library materials with statistical data that has been recorded. Constraints faced in procuring collections are budget deficits.